Effects of a Diagnosis-Related Group Payment Reform on Length and Costs of Hospitalization in Sichuan, China: A Synthetic Control Study - Liu Y; Du S; Cao J; Niu H; Jiang F; Gong L (Dove Medical Press, 2024)
Yaqing Liu,1,2 Sixian Du,1 Jianbo Cao,1 Haoran Niu,1 Feng Jiang,1 Liwen Gong1 1School of Medicine and Health Management, Huazhong University of Science and Technology, Wuhan, Hubei, People's Republic of China; 2Huazhong University of Science and Technology's Double First-Class Discipline Platform in Humanities (Research Center for Hospital High-Quality Development), Wuhan, Hubei, People's Republic of ChinaCorrespondence: Sixian Du, School of Medicine and Health Management, Huazhong University of Science and Technology, 5th Floor, No. 13 Hangkong Road, Qiaokou District, Wuhan, Hubei, 430030, People's Republic of China, Tel +8618271878646, Email dusixian16@163.comBackground: Diagnosis-related group (DRG) payment policies are increasingly recognized as crucial instruments for addressing health care overprovision and escalating health care costs. The synthetic control method (SCM) has emerged as a robust tool for evaluating the efficacy of health policies worldwide.Methods: This study focused on Panzhihua city in Sichuan Province, a pilot city for DRG payment reform implementation, serving as the treatment group. In contrast, 20 nonpilot cities within the province were utilized as potential control units. A counterfactual control group was constructed to evaluate the changes in average inpatient stay duration and health care organization costs following the DRG payment reform initiated in 2018.Results: Focusing on Panzhihua, Sichuan Province, the analysis reveals that following the reform in March 2018, the average length of hospital stay in Panzhihua decreased by 1.35 days during 2019- 2021. Additionally, the average cost per hospitalization dropped by 855.48 RMB, the average cost of medication per hospitalization decreased by 68.51 RMB, and the average cost of diagnostic and therapeutic procedures per hospitalization declined by 136.37 RMB. While global evidence backs DRGs for efficiency and cost reduction, challenges persist in addressing emerging issues like new conditions.Conclusion: Since its introduction in 2018, the DRG payment reform in Sichuan Province has effectively reduced both the duration of hospital stays and the operational costs of health care facilities. However, potential drawbacks include compromised service quality and an elevated risk of patient readmission, indicating a need for further refinement in the implementation of DRG payment reforms in China.Keywords: synthetic control method, health policy evaluation, diagnosis-related grouping, DRG, average hospitalization days, average hospital costs, China